Optimisation of citric acid production from a novel strain of aspergillus niger by submerged fermentation - Zakry Fitri, Ab Aziz (The Italian Association of Chemical Engineering, 2015)
Fungi isolated from various rotten fruits and vegetables were screened for the capability of producing citric acid. Aspergillus niger (A. niger) was obtained in the decayed onion peels and denoted as KON13 and this fungi strain was used in the production of citric acid by submerged fermentation. Critical process parameters affecting the fermentative citric acid production were investigated, including the types of carbon source, initial pH and initial sugar concentration in the fermentation medium. It was demonstrated that sucrose is the best carbon source in the fermentation process for this new isolate with a produced citric acid concentration of 1.76 g/L as compared to glucose and lactose. The study of the effect of initial pH within the range of pH 2 to 7 in the fermentation medium revealed that a maximum concentration of 1.82 g/L of citric acid was produced at an initial pH of 2. The highest citric acid concentration of 2.02 g/L was achieved at an initial sugar concentration of 140 g/L in the fermentation medium. This present study has demonstrated that the novel isolate strain of A. niger from onion peels is capable of producing citric acid with optimum concentration when sucrose was selected as the carbon source in the fermentation process, and at the fermentation conditions where initial pH of 2 and initial sugar concentration of 140 g/L in the fermentation medium.